Diversity and detections of Phytophthora species from trade and non‐trade environments in Ireland. (24th October 2016) - O'Hanlon, R.; Choiseul, J.; Corrigan, M.; Catarame, T.; Destefanis, M.
Abstract : The genus Phytophthora is one of the genera of organisms that poses the most threat to plant health worldwide. Statutory monitoring for Phytophthora species focuses on the species regulated in the European Union and recommended for regulation by EPPO (Plant Health Directive 2000/29 EC and the EPPO A2 List). This research provides details of the Phytophthora species detected from trade and non‐trade environments in Ireland between 2013 and 2015. The results of statutory surveys for the regulated species Phytophthora ramorum, Phytophthora kernoviae and Phytophthora lateralis from 2003 to 2015 are also presented. Testing of more than 11 000 samples was carried out using morphological and/or DNA identification with specifically designed Phytophthora conserved primers. This led to the detection of 19 species and 3 informally designated taxa of Phytophthora, including 8 new records for Ireland. Eight species were found in both trade and non‐trade locations, and three informally designated taxa were also detected. Phytophthora ramorum was found on the most hosts (30 hosts), followed by Phytophthora syringae (6 hosts) and Phytophthora kernoviae (3 hosts). Rhododendron was the host on which Phytophthora species were most frequently detected (12 Phytophthora species). The role of the plant trade in spreading invasive Phytophthora species is discussed.